Ecosystem Exchange, Strategic Capabilities, and Firm Performance with Agility and Innovation Mediators - Hendrawidjaja, Josef Budi; Soetjipto, Budi Widjaja; Kusumastuti, Ratih Dyah; Jayanagara, Oscar (Pandawan, 2026)
Understanding the ecosystem remains a big issue, especially in coping with the affiliation challenges of the ecosystem actors. Relied upon open system, resource-based, and exchange theory, this study aims to depict the role of ecosystem exchange and Organizational Strategic Capabilities (OSC) and the relationship with strategic agility and service innovation in enhancing firm performance, as well as its mechanism in portraying process view of Resource-Based Theory (RBT) as the search for alignment strategy to multi-actors’ challenges in the multilateral ecosystem. This study was conducted by using a quantitative research approach to examine sets of hypotheses. Applying five-point Likert-scale questionnaires, the primary data were collected from 196 Indonesian medical devices distributor companies. Then, the structural equation modelling was used to analyze the data. This study found strategic capabilities display impressively the autonomous merit of the firms and how the firms communicate through ecosystem exchange. While revealing the principle of equifinality, all roads lead to Rome, of the firms as an open system. This study portrays how the firms do exchange intangible resources socially and tangible resources economically and establish solid alignments with their ecosystem, hence keeping the competition away. Indonesian medical device distributor firms can achieve superior performance by fostering ecosystem exchange, developing strategic capabilities, and crucially building strategic agility. These findings offer actionable insights for industry leaders and policymakers aiming to strengthen the healthcare supply chain and advance progress toward the SDGs. The research also provides a foundation for future studies exploring the interplay of dynamic capabilities and innovation in other sectors and contexts.